Role of diffusion‐weighted magnetic resonance imaging in the evaluation of scalp dermatofibrosarcoma protuberans. (28th December 2015) - Van Steenkiste, Eva; Van Laethem, An; Biesemans, Geert; Pans, Steven
Abstract: Background: Dermatofibrosarcoma protuberans (DFSP) is a rare tumor that grows with tentacle‐like projections. In particular, on the scalp this could explain the frequent incomplete resections and the high rate of multiple local recurrences. Adequate pre‐ and postoperative imaging methods to visualize these prolongations are required to determine the extent of the tumor and to intercept recurrences in a short time base. Methods: A retrospective study was performed on two cases of multiple recurrent scalp DFSP. The use of diffusion‐weighted imaging (DWI) for pre‐ and postoperative assessment of DFSP was evaluated. Results: Diffusion‐weighted imaging magnetic resonance imaging was able to visualize the horizontal extent of tumor prolongations in the periosteum. Also, residual tumor tissue was distinguished from scar tissue in a large area of previous surgical interventions. Conclusion: We found DWI magnetic resonance imaging a valuable tool in planning the multidisciplinary therapeutic approach and follow‐up of DFSP on the scalp.